DEVELOPMENT OFRIZATRIPTAN BENZOATE MICROSPHERES FOR NOSE TO BRAIN TARGETING - Butani, Shital; Shah, Tora; Parmar, Kunal; Rajput, Amarjitsing (International Journal of Applied Pharmaceutics, 2016)
Objective: Oral administration of rizatriptan benzoate shows poor bioavailability due to first pass metabolism, which can be avoided by nasal administration of drugs. Additionally, the nasal administration provides faster onset of action, which is desired to get relief from the intense pain of a migraine. The present research work was emphasised on design, development and evaluation of mucoadhesive microspheres for nasal delivery of rizatriptan benzoate through a systematic approach. Methods: The microspheres of rizatriptan benzoate were prepared by the w/o/w double emulsion solvent diffusion method using the non-aqueous medium. Critical formulation and process parameters were identified through preliminary trial batches and 2[4-1] fractional factorial design was employed using polymer concentration (X1:2-5%), drug to polymer ratio (X2:1:2-1:6), amount of liquid paraffin (X3:100-200 ml) and the amount of magnesium stearate (X4:100-150 mg) as independent variables. Results: Design batches were evaluated for percent yield (50-78%), percent entrapment efficiency (62-85%), drug loading (7.5-30%), % mucoadhesion (47-75%) and drug release at 6 h (44-78%). Scanning electron microscopic (SEM) study showed that microspheres were of 50 Âµm in size and spherical in shape with a smooth surface. The optimised batch (D10) showed 85% entrapment efficiency and 66.6% drug release within 6 h. The developed microspheres could be used to deliver rizatriptan benzoate through nasal administration for treatment of a migraine. Conclusion: The developed microspheres can be considered as a promising system for nasal delivery system of rizatriptan benzoate